The Cytogenetic Effects on Peripheral Blood Lymphocytes in Cancer Patients After Radiation Therapy: Chromosome Aberrations and Micronuclei - Lusiyanti, Yanti; Surniyantoro, Harry Nugroho Eko; Rahajeng, Nastiti; Suvifan, Viria Agesti; Purnami, Sofiati; Choridah, Lina (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2021)
Individual responses to radiotherapy are often observed whether or not regimes with identical treatments were applied. Patient-related factors, the therapeutic process, and therefore the intrinsic factors of individual radiosensitivity are considered to be causing the variability of side effects. A preliminary evaluation was done on cytogenetic biomarkers found in cancer patients. The purpose of this present study was to assess the individual response of patients with cancers after radiation therapy. The sample obtained from 11 patients with different types of cancer as a case group and 12 people as a control group from a healthy volunteer. Blood samples were stimulated by an in vitro culture using phytohemagglutinin, and the cultures were assessed by using the Dicentric and Cytokinesis- Block Micronucleus (CBMN-) assay. These two methods were compared. The results showed that the overall dicentric chromosome and micronuclei in binucleate cells (MN/BNC) have a significantly higher frequency in the breast, head, and neck compared to extremity cancer. A high frequency of micronuclei in lymphocyte patients was seen after radiotherapy treatment but relatively not much higher compared to the range of micronuclei backgrounds in healthy people The CBMN is the most effective assay for evaluation of the cytogenetic studies in cancer patients because it is more radiosensitive to study individual responses. By evaluating the effects of radiotherapy based on DNA damage, the severity of radiation exposure can be studied. This study can be useful for researchers and related stakeholders in the application of radiotherapy.